Reversible phase transition and switchable dielectric behaviors triggered by rotation and order-disorder motions of crowns. Issue 11 (16th February 2018) - Liu, Yi; Zhou, Hai-Tao; Chen, Shao-Peng; Tan, Yu-Hui; Wang, Chang-Feng; Yang, Chang-Shan; Wen, He-Rui; Tang, Yun-Zhi
Abstract : Compound1 shows apparent step-like dielectric changes near the phase transition, which are triggered by the synergetic rotation motion of 18-C-6 crown ether cycles and hexafluorophosphate anions. Abstract : Solid-to solid-state reversible phase transitions are widely used in switchable dielectrics, ferroelectrics, piezoelectrics, and pyroelectric and non-linear optical materials. Herein we report a new crown ether clathrate, [Habf-(18-crown-6)1.5 ] + [PF6 ] − (Habf = p -ammonium benzene formamide) which shows an interesting reversible phase transition near room temperature (263 K). X-ray single crystal diffraction analysis shows that the synergetic rotation motion between the 18-crown-6 crown ethers and the order–disorder motions of both hexafluorophosphate guest anions and 18-crown-6 crown ether host molecules lead to the phase transition. This reversible phase transition is confirmed by an evident thermal anomaly behavior around 263 K. The apparent step-like dielectric change around the phase transition indicates that it has potential application in dielectric switches.